The Effect of System Quality and Innovative Features of the BYOND by BSI Application on Customer Satisfaction at Bank Syariah Indonesia in Surabaya - Rismaya Arimatu Duqa; Siti Masruroh (CV. Muris Global Education, 2026)
The rapid development of information and communication technology has significantly transformed various sectors, including business and financial services. These changes have encouraged the banking industry to continuously innovate and adapt its marketing strategies to remain competitive. One such strategy is the enhancement of digital services. Bank Syariah Indonesia introduced the BYOND by BSI application in 2024 as a replacement for BSI Mobile. This SuperApp is designed to improve service efficiency, customer convenience, and transaction support. This study aims to examine the effect of system quality and innovative features of the BYOND by BSI application on customer satisfaction in Surabaya. The research employs a causal associative quantitative method. A sample of 100 respondents was determined using the Lemeshow formula due to the unknown population size. Data were collected through questionnaires distributed via social media platforms and analyzed using descriptive statistics and SPSS. The results indicate that system quality and innovative features have a positive and significant effect on customer satisfaction, with innovative features having a more dominant influence.